Keystone design perforator island flap: our experience for coverage of lower limb defects (Bangladesh Journal of Medical Science, 2023)
The fusion of concept of perforasome and trapezoid design made Keystone design Perforator Island flap (KDPIF). This flap was first introduced by Behan in 2003 and since then many modifications were done. Keeping the principles of KDPIF, two modifications were done in this study.Aims: to determine reliability and advantages of KDPIF for lower limb defect coverage.Materials and Methods:15 cases were done in Plastic surgery department of Rajshahi Medical College Hospital from October 2020 to September 2022.Results: The largest wound measuring 11X 10 cm2 on thigh defect following wide local excision of sarcoma was covered by the largest dimension flap measuring 16X 11 cm2. In most of the cases (7 cases), Type IIA KDPIF was done. With co-morbidities, 14 flaps survived without any complications. Range operating time was 35-110 minutes.Conclusion: Due to its reliable vascularity and easy execution and good outcomes, KDPIF is one of the best choices for lower limb defect coverage.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 920-925